Students Perception of the Cake Application as a Medium to Enhance English Speaking - Haque, Arina Amelia; Permanasari, Pradnya (Pusdikra Publishing, 2025)
In the current era of globalization, the ability to speak English is a very important skill to master because it is an international language used to communicate between nations. However, many students still experience difficulties in learning English, especially in speaking skills. These difficulties include pronunciation errors, lack of vocabulary mastery, and low confidence in speaking. This study aims to investigate students' perceptions of the use of Cake application in improving their English speaking skills. This study was conducted on students of class XI.3 SMAN 1 Wiradesa and involved 12 students as participants. The method used was descriptive qualitative with data collection techniques through questionnaires and interviews. The results showed that most of the students gave positive perceptions towards the use of Cake application. They found the app effective in helping to improve pronunciation, fluency and confidence. Features such as native speaker videos, speech recognition technology, and interactive exercises also encourage students' self-learning motivation. Based on these findings, it can be concluded that the Cake app is a potential supplementary learning medium in English language learning, particularly for improving speaking skills. The study recommends that teachers consider integrating this app in the learning process and provide guidance on its use.